Endoscopic Retrograde Cholangiopancreatography at Dhulikhel hospital: Outcome Analysis - Gurung, RB; Purbey, B; Koju, R; Bedi, TRS (Kathmandu University Medical Journal, 2015)
Background Endoscopic Retrograde Cholangiopancreatography (ERCP) is an important but potentially invasive therapeutic procedure in treating various pancreatobiliary conditions. In Nepal, the ERCP services is limited to a few tertiary care centers mostly in the capital, Kathmandu. Dhulikhel hospital has started ERCP since 2011 providing services to patients from all over the country. The study analyzes the outcome from data since August 2011 to 2013 August.Objective To analyze the results of ERCP done in Dhulikhel hospital, Kathmandu University hospital.Method This is a retrospective study. The ERCP records of all the patients done since August 2011 to August 2013 were retrieved. A total of 516 attempts of ERCP were done since August 2011 to August 2013. Out of these, 423 were included for the analysis. The repeat ERCP for the same patient due to failed cannulation or patients undergone ERCP but incomplete documentation were excluded. The demographic data, indications, the findings, the outcome in terms of success or failure to cannulation, success or failure of stone extraction, stenting and complications were all derived and analyzed. SPSS 16 version was employed for data management and analysis.Result The female: male ratio was found to be 1.7 : 1. The mean age of patients were 50.57±17.8 Years. The most common indication for ERCP were: choledocholithiasis 208(49.17%); followed by: obstructive jaundice 69(16.3% ) of undetermined cause, acute biliary pancreatitis 26(6.4%), suspected bile duct injury during cholecystectomy 18(4.2%), periampullary growth 21( 4.96%), Cholangiocarcinoma 12(2.8%), chronic pancreatitis 10( 2.3%), CBD stent exchange 23(5.43%), dilated cbd 21(4.96%) , acute cholangitis 14(3.3%).The most common finding was CBD stone in 308(72.81%), normal in 51(12.1% ), bile duct stricture in 45(10.63%). Bile duct injury during cholecystectomy was found in 13(3.1%), biliary obstruction due to ampullary growth and pancreatic head mass was found in 21(4.96%) and 6(1.41%) respectively. Choledochal cyst was found in 5(1.2%), chronic pancreatitis in 7(1.7%). Biliary fascioliasis was found in one (0.24%); and roundworm in 1(0.24).The most common complication was acute pancreatitis in 17(4%), post-ERCP cholangitis 6(1.4%), bleeding 6(1.4%), duodenal perforation in 1(0.2%), arrhythmia in 1(0.2%) and one death (0.2%).Conclusion ERCP has been a potentially emerging therapeutic tool for various pancreato-biliary disorders in Nepal.Kathmandu University Medical Journal Vol.12(1) 2014: 55-59